1998
DOI: 10.1021/bi980832y
|View full text |Cite
|
Sign up to set email alerts
|

The Activation State of p38 Mitogen-Activated Protein Kinase Determines the Efficiency of ATP Competition for Pyridinylimidazole Inhibitor Binding

Abstract: The serine/threonine kinase p38 is a ubiquitous, highly conserved, stress responsive, signal-transducing enzyme. It regulates the production of proinflammatory mediators and is the target of the cytokine synthesis inhibitory pyridinylimidazoles. We have expressed human p38 in Drosophila S2 cells and characterized preparations of mixed unphosphorylated/monophosphorylated (inactive) and homogeneously diphosphorylated (active) forms of the enzyme. We observed that only the active preparation of the enzyme has sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
111
3
4

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(139 citation statements)
references
References 29 publications
21
111
3
4
Order By: Relevance
“…It has been shown that PD98059 prevents ERKs phosphorylation/activation by inhibiting mitogen-activated protein kinase/extracellular signal-regulated kinase kinase activity (30). SB203580 was first described as an inhibitor of p38 MAPK activity by competing with ATP for binding (31), but it was later demonstrated that the drug also prevents p38 MAPK phosphorylation/activation (32). We observed that treatment of U-937 cells with 30 M PD98059 totally abolished ERK phosphorylation, whereas treatment with 5-20 M SB203580 (because higher concentrations were toxic) only partially inhibited p38 MAPK phosphorylation (Fig.…”
Section: Effect Of Kinase Inhibitors On Apoptosis-the Rapid Increase mentioning
confidence: 99%
“…It has been shown that PD98059 prevents ERKs phosphorylation/activation by inhibiting mitogen-activated protein kinase/extracellular signal-regulated kinase kinase activity (30). SB203580 was first described as an inhibitor of p38 MAPK activity by competing with ATP for binding (31), but it was later demonstrated that the drug also prevents p38 MAPK phosphorylation/activation (32). We observed that treatment of U-937 cells with 30 M PD98059 totally abolished ERK phosphorylation, whereas treatment with 5-20 M SB203580 (because higher concentrations were toxic) only partially inhibited p38 MAPK phosphorylation (Fig.…”
Section: Effect Of Kinase Inhibitors On Apoptosis-the Rapid Increase mentioning
confidence: 99%
“…In these cells, T-cell receptor (TCR) ligation results in activation of the Zap70 pathway, which subsequently results in the phosphorylation of Tyr323 on P38 and induction of the intramolecular P38 activity (Salvador et al, 2005). The dual phosphorylation of P38 mediated via MKKs is insensitive to inhibition of P38 by SB203580, which action lies in occupation of the ATP-binding pocket within the P38 kinase domain (Lee et al, 2000;Kumar et al, 1999;Gum et al, 1998;Frantz et al, 1998). However, P38 phosphorylation under conditions of TAB1 association or Tyr323 phosphorylation is sensitive to SB203580 (Ge et al, 2002;Salvador et al, 2005;Kim et al, 2005) indicating that this phosphorylation of P38 occurs via P38 mediated autophosphorylation.…”
Section: Introductionmentioning
confidence: 99%
“…Wie Abbildung 3 zeigt, bindet p38a den Inhibitor SB202190 (331 Da) mit K D = (48 AE 21) nm, was den Literaturwert von 37 nm wiedergibt. [21] Die Obergrenzen der Affinität zu PD169316 (360 Da) und SB239063 (368 Da) wurden zu 33 nm bzw. 20 nm bestimmt.…”
unclassified
“…Diese Ergebnisse stimmen gut mit den Literaturwerten überein. [21][22][23] Hitzedenaturierte p38a zeigte keine Bindung (Kontrolle).…”
unclassified
See 1 more Smart Citation